Aplikasi Android Pencarian Coffee Shop Terbaik Menggunakan Metode Weighted Product - Hasbiyah, Nina; Rifqi Ma’arif, Muhammad; Bayu Saputra, Andika; Alfi Sa'diya, Nafisa (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Coffee Shop is a place to gather and relax with family, friends, relatives to enjoy the weekend or just to unwind from the activities that have been carried out. Currently, there are many coffee shops in Sleman that provide products at affordable prices and comfortable places, so that many students make coffee shops an alternative place to complete assignments. However, many people still ask about the Coffee Shop along with detailed information such as taste, price, service, atmosphere, and distance. The Weighted Product method is one of the weighting methods, where multiplication is used to connect attribute ratings, and the rating of each attribute must be raised first with the weight of the attribute in question. The results of this study are in the form of an Android application to find the best Coffee Shop using the Weighted Product method so that it can make it easier for people to choose a Coffee Shop based on the selected criteria. The application is built using the Dart programming language and utilizes the Flutter framework and MySQL as a database management system.